2007
DOI: 10.1128/iai.00392-07
|View full text |Cite
|
Sign up to set email alerts
|

σ B and the σ B -Dependent arlRS and yabJ-spoVG Loci Affect Capsule Formation in Staphylococcus aureus

Abstract: The alternative transcription factor B of Staphylococcus aureus affects the transcription of the cap gene cluster, required for the synthesis of capsular polysaccharide (CP), although this operon is lacking an apparent B -dependent promoter. Regulation of cap expression and CP production in S. aureus strain Newman was shown here to be influenced by B , the two-component signal transduction regulatory system ArlRS, and the yabJ-spoVG locus to different extents. Inactivation of arlR or deletion of the sigB opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 60 publications
2
79
1
Order By: Relevance
“…The molecular mechanisms of YabJ, which belongs to the YjgF protein family of unknown biochemical function (49), and of the stage V sporulation protein G SpoVG (30), originally identified in Bacillus subtilis as being involved in the formation of the spore cortex, are yet unknown for the nonsporulating S. aureus. However, the finding that inactivation of the staphylococcal yabJ-spoVG operon, like inactivation of B , reduces the transcription of the capA gene, which is not preceded by a B promoter (36), and reduces the resistance level of methicillin-resistant S. aureus (MRSA) and glycopeptide intermediate-resistant S. aureus (GISA) (46) support the hypothesis that the yabJ-spoVG operon may encode a B downstream regulatory element. Early work on B activity in S. aureus showed that extracellular nuclease and lipase activities are negatively regulated by the alternative sigma factor B via a yet unknown indirect mechanism (31).…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…The molecular mechanisms of YabJ, which belongs to the YjgF protein family of unknown biochemical function (49), and of the stage V sporulation protein G SpoVG (30), originally identified in Bacillus subtilis as being involved in the formation of the spore cortex, are yet unknown for the nonsporulating S. aureus. However, the finding that inactivation of the staphylococcal yabJ-spoVG operon, like inactivation of B , reduces the transcription of the capA gene, which is not preceded by a B promoter (36), and reduces the resistance level of methicillin-resistant S. aureus (MRSA) and glycopeptide intermediate-resistant S. aureus (GISA) (46) support the hypothesis that the yabJ-spoVG operon may encode a B downstream regulatory element. Early work on B activity in S. aureus showed that extracellular nuclease and lipase activities are negatively regulated by the alternative sigma factor B via a yet unknown indirect mechanism (31).…”
mentioning
confidence: 72%
“…For this purpose we complemented SM148 and the B mutant IK184 with either gene separately or both genes together, expressed from the B -independent constitutive promoter. In analogy to the complementation of capA transcription in a ⌬yabJ-spoVG background, where SpoVG was shown to be the effector of the yabJ-spoVG operon (36,46), the plasmids pspoVG and pyabJspoVG did largely restore nuc expression (27). Sequences matching the GNNTNN-12-15-NGGTAN consensus, with no more than three mismatches of the degenerated bases from the GTTTAA-12-15-GGGTAT sequence and lying within a range of 500 bp upstream of the ORF were accepted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deletion of the msaABCR operon alters the expression of several global regulators, including sarA, agr and sigB, all of which have been shown to be indirectly involved in capsule production (Bischoff et al, 2004;Pané-Farré et al, 2006;Meier et al, 2007;Dassy et al, 1993;Sahukhal & Elasri, 2014). The regulatory mechanism for msaABCR has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%